2018
DOI: 10.1002/sia.6454
|View full text |Cite
|
Sign up to set email alerts
|

Band gap tailoring of chemically synthesized lead sulfide thin films by in situ Sn doping

Abstract: In the present report, undoped and tin (Sn)-doped lead sulfide thin films were synthesized via chemical bath deposition method. The effects of Sn molar concentration on the optical, structural, and morphological properties were systematically studied. The concentration of Sn in the chemical bath was characterized by the ratio of [Sn +2 ]/[Pb +2 ] and varied from 0 to 15 at.%. Both doped and undoped thin films were polycrystalline in nature with a face-centered cubic crystal structure; however, the preferred or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Among them, one-dimensional semiconductor phosphor nanocrystal structures have been extensively studied for the last two decades because of their unusual structural, electronic, and optical properties [3]. Lead sulfide (PbS) is among the IV-VI group semiconducting material with direct band gap of 0.41 eV at room temperature and a space group of Fm3m [4]. Moreover, its absorption coefficient continuously increases from the infrared to the visible region [5].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one-dimensional semiconductor phosphor nanocrystal structures have been extensively studied for the last two decades because of their unusual structural, electronic, and optical properties [3]. Lead sulfide (PbS) is among the IV-VI group semiconducting material with direct band gap of 0.41 eV at room temperature and a space group of Fm3m [4]. Moreover, its absorption coefficient continuously increases from the infrared to the visible region [5].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the decreased film thickness with an increase in Sn salt concentration in the solution (Table 1). Hone et al [17] also observed the decreased grain size of PbS films with increased Sn-doping concentration. For the better physical and chemical properties of the PbS, the crystalline growth should be uniform.…”
Section: Microstructurementioning
confidence: 87%
“…Doping is an effective technique to modify the optical, electrical and structural properties of the semiconductor materials. As reported, doping of certain rare earth elements and transition metals can alter the optical band gap, the carrier density and the electrical resistivity of PbS thin films [16,17]. Several research groups have tested different dopant elements such as Ag, Al, Cu, Cd, Zn, Sb, Sn, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous methods such as spray pyrolysis [9], thermal evaporation [8], hot wall vacuum deposition [10], hot-wall epitaxy [11], chemical bath deposition [2,12,13] and successive ionic layer adsorption and reaction (SILAR) [14], have been used to synthesize PbSnS. However, there are relatively very few publications on the deposition of the ternary PbSnS by electrochemical deposition.…”
Section: Introductionmentioning
confidence: 99%